A fragile public preference for cyber strikes: Evidence from survey experiments in the United States, United Kingdom, and Israel. Issue 2 (3rd April 2021) - Shandler, Ryan; Gross, Michael L.; Canetti, Daphna
ABSTRACT: To what extent does the public support the use of cyber weapons? We propose that public exposure to the destructive potential of cyber-attacks will dispel the clear cross-national preference for cyber strikes. To test this, we conducted two survey experiments ( n = 2, 585) that examine support for cyber versus conventional military strikes in the United States, United Kingdom, and Israel. In study 1, we exposed respondents to television news reports depicting various forms of terror attacks, and then measured the subsequent support for retaliatory options. Findings indicate that the high public support for deploying cyber weapons dissipated entirely among respondents exposed to lethal cyber-attacks. In study 2, we probed this vanishing support, finding that exposure to destructive cyber-attacks undercuts the perception of cyber as a less lethal domain, therefore diminishing its appeal. We conclude by discussing how the fragile public preference for cyber weapons encourages military escalation in the short-term.